Pengaruh kepuasan kerja dan motivasi terhadap kinerja pegawai pada Kantor Sekretariat DPRD Kabupaten Batanghari - Veronica, Vetty; Edward, Edward; Wilian, Rohman (Jurnal Dinamika Manajemen, 2021)
This study aims to determine the effect of job satisfaction and motivation on employee performance. This research is a survey research type with the sample in this study amounting to 43 employees of the Secretariat Office of the DPRD Batanghari Regency. The data collection method uses a questionnaire and is measured by a Likert scale. The data testing technique used in this research includes instrument test (validity test, reliability test), multiple linear regression analysis, t test, F test and determination coefficient test (R2) with the help of the SPSS application. The findings of this study have the results of research that partially show that job satisfaction has a positive and significant effect on the employee performance of the Batanghari DPRD secretariat office and work motivation has a positive and significant effect on the employee performance of the Batanghari DPRD secretariat office. Simultaneously, it shows that Job Satisfaction and Work Motivation have a positive and significant effect on Employee Performance of the Batanghari DPRD Secretariat Office.